PENGARUH SENAM LANSIA TERHADAP PERUBAHAN GLUKOSA DARAH PADA MAJELIS TA’LIM BABUSSALAM - Mawar Wulandari; Andi Atssam Mappanyukki; Ichsani Ichsani (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
The purpose of the study was to determine the effect of elderly exercise on changes in blood glucose. This study knowing a causal relationship where elderly exercise was the cause and decreased blood glucose as the effect. So this study can be classified into quantitative research with the type of Pre-Experimental Design. The results of descriptive analysis of the data on the effect of elderly exercise on changes in blood glucose at the Ta'lim Babussalam Rappocini assembly, Makassar City. Preliminary data on glucose before doing exercise for the elderly obtained an N value of 15, a range of 192.00, a minimum value of 70.00, a maximum of 262.00, a sum value of 1992.00, a mean (average) value of 1.32802 standard deviation of 50.91618 and a variance of 2.5923. The final data on glucose after doing exercise in the elderly obtained an N value of 15, a range of 67.00, a minimum value of 83.00, a maximum of 150.00, a sum value of 1766.00, a mean (average) value of 1.17732, a standard deviation of 20.10852 and a variance of 404.352. The results of testing the normality of the data on the effect of elderly exercise on changes in blood glucose at the Ta'lim Babussalam Rappocini assembly in Makassar City using the Kolmogorov Smirnov test showed the following results: Glucose data before doing Elderly exercise obtained absolute values of 0.232, positive 0.232, negative -0.109, Kolmogorov-Smirnov 0.898 ,Asymptote. Sig0.396 (P>0.05), it can be said that the data follows a normal distribution or is normally distributed. Blood glucose data after doing elderly gymnastics obtained absolute value 0.109, positive 0.103, negative -0.109, Kolmogorov-Smirnov 0.424, Asymptot. Sig0.994 (P>0.05), it can be said that the data follows a normal distribution or is normally distributed.